ORGANIC CARBON IN THE SEDIMENTS OF THE LOWER REACHES OF PERIAR RIVER - SARALADEVI, K.; VENUGOPAL, P.; SANKARANARAYANAN, V. N. (Journal of Indian Fisheries Association, 2015)
Sediments are indicators of the quality of water overlying them and hence, useful in theassessment of environmental pollution. Temporal and spatial variations in sedimentcharacteristics and organic carbon content from 9 stations in the lower reaches of Periyarriver an area in Cochin Backwater which is polluted from different sourcesÂ· were studiedfor one year during 1981. Variations in colour and texture of sediments were brought aboutby changes in the grain size and state of oxidation of organic matter. The colour of thesediment varied from greyish black at stations 1 and 2, brownish at station 3, black atstations 4 to 8 and reddish at station 9.Organic carbon and sediment texture showed a direct relationship at all stations exceptat station 9 where organic carbon content showed an irregular pattern. Overall range oforganic carbon content was between 1.19 and 29.6 mg.g-1â€¢ The mean organic carbon of thestations ranged between 6.8 mg.g-1 (station 5) and 20.8 mg.g-1 (station 9). On the wholetemporal variations were considerable with high values at station 9 and low values at station5. Fluctuations were more at stations 6,7 and 8.